Severe Malaria: A Case of a Significant Rapid Rise in the Parasite Level. (16th March 2020) - Atere, Muhammed; Muzangwa, Lloyd; Munoh Kenne, Foma; Hanna, Cherry; Saverimuttu, Jessie; Kopetz, Virginia
Abstract : Malaria is transmitted by the Plasmodium parasite, and most of the cases reported in the United States are often as a result of patients with recent return from endemic areas. Prompt diagnosis and treatment, particularly if there is severe parasitemia and drug failure, is essential in preventing mortality. Our patient had an unusual rapid rise in parasite but susceptible to intravenous artesunate.